Study of PMFSM with Direct Drive Employing Two Counter Segmental and Salient Rotor for Wind Turbine - Mohammad Fauzi, Muhammad Ezzat Syahmie; Jenal, Mahyuzie (Evolution in Electrical and Electronic Engineering, 2024)
A wind turbine designed for harnessing electrical power from wind energy features a turbine rotor positioned for rotation in the wind and multiple blades converting wind force into rotational energy. The Flux Switching Machine (FSM), an innovative category of electric motors developed by previous researchers, has gained prominence in electrical AC motor applications. In the realm of wind turbines, employing a counter-rotating configuration with two rotor sets enhances power density twofold. The three types of FSMs include Permanent Magnetic Flux Switch Machines (PMFSM), Field Excitation Flux Switches (FEFSM), and Hybrid Excitation Flux Switches (HEFSM). PMFSM stands out for its affordability, primary outcome focus, and FEC-free winding with minimal copper losses, making it suitable for diverse performance requirements. This analysis delves into the design and investigation of a dual rotor PMFSM for a counter-rotating wind turbine. From a design perspective, the study explores various configurations of Permanent Magnet Flux Switching Machines (PMFSM), with a particular emphasis on PMFSM featuring segmented permanent magnets and a corresponding pole configuration. Additionally, PMFSM is examined with different inner and outer rotor positions, employing a dual rotor configuration with varied stator configurations to attain optimal torque, power, and speed levels for the motor. The dual rotor structure has emerged as a focal point in electrical machine research, promising improved output torque and power. conclusion, the findings from these investigations will be summarized at the conclusion of this chapter, providing a comprehensive overview of the research outcomes and their implications.